Mediterranean diet: The role of long-chain ω-3 fatty acids in fish; polyphenols in fruits, vegetables, cereals, coffee, tea, cacao and wine; probiotics and vitamins in prevention of stroke, age-related cognitive decline, and Alzheimer disease - Román, G.C.; Jackson, R.E.; Gadhia, R.; Román, A.N.; Reis, J. (Revue neurologique, 2019)
The mechanisms of action of the dietary components of the Mediterranean diet are reviewed in prevention of cardiovascular disease, stroke, age-associated cognitive decline and Alzheimer disease. A companion article provides a comprehensive review of extra-virgin olive oil. The benefits of consumption of long-chain ω-3 fatty acids are described. Fresh fish provides eicosapentaenoic acid while α-linolenic acid is found in canola and soybean oils, purslane and nuts. These ω-3 fatty acids interact metabolically with ω-6 fatty acids mainly linoleic acid from corn oil, sunflower oil and peanut oil. Diets rich in ω-6 fatty acids inhibit the formation of healthier ω-3 fatty acids. The deleterious effects on lipid metabolism of excessive intake of carbohydrates, in particular high-fructose corn syrup and artificial sweeteners, are explained. The critical role of the ω-3 fatty acid docosahexaenoic acid in the developing and aging brain and in Alzheimer disease is addressed. Nutritional epidemiology studies, prospective population-based surveys, and clinical trials confirm the salutary effects of fish consumption on prevention of coronary artery disease, stroke and dementia. Recent recommendations on fish consumption by pregnant women and potential mercury toxicity are reviewed. The polyphenols and flavonoids of plant origin play a critical role in the Mediterranean diet, because of their antioxidant and anti-inflammatory properties of benefit in type-2 diabetes mellitus, cardiovascular disease, stroke and cancer prevention. Polyphenols from fruits and vegetables modulate tau hyperphosphorylation and beta amyloid aggregation in animal models of Alzheimer disease. From the public health viewpoint worldwide the daily consumption of fruits and vegetables has become the main tool for prevention of cardiovascular disease and stroke. We review the important dietary role of cereal grains in prevention of coronary disease and stroke. Polyphenols from grapes, wine and alcoholic beverages are discussed, in particular their effects on coagulation. The mechanisms of action of probiotics and vitamins are also included.